From data to decisions: Strengthening African soil information systems - Accelerating Impacts of CGIAR Climate Research for Africa; CIFOR-ICRAF; CA4SH (2025)
This brief describes the importance of healthy soils and how they are central to achieving multiple Sustainable Development Goals. It notes the policy context for establishing robust soil information systems (SIS) in Africa. The brief gives an overview of current challenges with soil health data, underscoring the importance of holistic indicators. It further elaborates why robust SISs are essential, highlighting their key functions. The brief ends by emphasising the benefits of adopting harmonised soil health indicators, strengthening SISs, and making data openly accessible.